Automatic cloth retriever system - Nur Idayu, Hamzah (2010)
For a working couple, it is hard to find time to have laundry day where the cloth is dried through the whole day because the weather can change from sunny to rainy days. This projects use Microcontroller PIC 16F877 to install all program that will give instructions to conduct this system properly. This project will automatically retrieve-out the clothes when it is the sunny day and oppositely retrieve-in the clothes when it is a rainy day. This part needs DC motor to convert electrical power into mechanical power for retrieve-out and retrieve-in all the clothes. Temperature sensors that will be use in this project can measure temperature and day condition whether it is sunny or rainy day more accurately. LDR (Light Dependent Resistor) sensors will be use to detect light. Rain detector also will be use to sense when it begins to rain outside by detecting rain water from moisture impedance sensor locate at the rod. The dry-time of the clothes will be setup using rotary knob switch and it will automatically retrieve-in the clothes using DC motor when the dried-time is finished. This project will be display the day condition, temperature and dry-timer using LCD (Liquid Crystal Display) or indicator light such as LED (Light Emitting Diode).